Trasparenze ed epifanie Quando la luce diventa letteratura, arte, storia, scienza - GRAZIANI, Michela (Biblioteca di Studi di Filologia Moderna, 2016)
The volume Trasparenze ed epifanie. Quando la luce diventa letteratura, arte, storia, scienza ("Transparencies and epiphanies. When light becomes literature, art, history, science") brings together thirty contributions presented at the interdisciplinary conference organized at the University of Florence on the occasion of the International Year of Light 2015. Scholars in the fields of science, history, history of art and cinema, philosophy, philology, Italian and foreign literature and literature literary theory from seven departments of the Florentine university introduce various meanings and symbolic representations of the concept light during the ancient, medieval, modern and contemporary epoch. Moreover, they also propose a common "luminous journey" in the civilisation of open scientific and cultural discussion.